ภาพลักษณ์ทางร่างกายของวัยรุ่นชายไทย : ศึกษากรณีนิสิตชายระดับปริญญาตรีของจุฬาลงกรณ์มหาวิทยาลัย - ธีรพล วุฒิทวีพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this study is to examine body image of Thai adolescents. The study explored two hypothesis : (1) the relationship between family and ideal body image (2) the relationship between peer and ideal body image (3) the relationship between mass media and ideal body image (4) the relationship between family and self interest in one’s own body image (5) the relationship between peer and self interest in one s own body image (6) the relationship between mass media and self interest in one s own body image (7) the relationship between family and body image satisfaction (8) the relationship between peer and body image satisfaction (9) the relationship between mass media and body image satisfaction (10) the relationship between body image dissatisfaction and body management (11) between group of heterosexual and homosexual have the different in body management. Quantitative data was made possible through survey questionnaire. The quantitative samples consisted of 200 male undergraduate chulalongkorn university students. For data analysis, descriptive statistic, percentage, frequency, arithmetic mean, and standard deviation were used to describe demographic characteristics. Chi-square correlation coefficient was used to test relationship of the variables. The findings term hypothesis testing revealed that: (1) Family have a significant relationship to the ideal body image. (2) Peer have a significant relationship to the ideal body image. (3) Mass media have a significant relationship to the ideal body image. (4) Family have a significant relationship to the self interest in one’s own body image. (5) Peer have a significant relationship to the self interest in one’s own body image. (6) Mass media have a significant relationship to the self interest in one’s own body image. (7) There was no significant relation between family and body image satisfaction. (8) There was no significant relation between peer and body image satisfaction. (9) There was no significant relation between family and body image satisfaction. To complete the picture of what the quantitative data showed, the research selected twelve male Chulalongkorn undergraduate students who filled in the survey question are for further in-depth interviews, the descriptive data revealed that: (10) Body image dissatisfaction has a significant relationship to the body management. (11) Group of heterosexual and homosexual have the different in body management.